PERAMALAN MINYAK KELAPA SAWIT DENGAN PEMULUSAN EKSPONENSIAL DI PABRIK KELAPA SAWIT CIKASUNGKA PT. PERKEBUNAN NUSANTARA VIII - Puspitaningrum, Adhelia; Abadi, Slamet; Wijaya, I Putu Eka (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Palm (Elaeis guineensis Jacq) is a commodity that has an important role in the plantation sub-sector, especially in Indonesia. Palm oil has always contributed greatly to national income. The production of palm oil can change every period. The purpose of this research is to predict palm oil production at PTPN’s Cikasungka Palm Oil Mill. The research metod is Single Exponential Smoothing dan Double Eksponential Smoothing. This research uses primary data and secondary data. The primary data collection was conducted by interview techniques. The respondences of this study were employees of the Cikasungka Palm Oil Mill office and other needed sources. Secondary data was obtain from the Central Agency of Statistics. Processed data using application called Minitab. First, the best alpha will be found by trial and error one by one, then the best alpha will be used to forecasting. The best alpha is 0,5 for single and double exponentials smoothing. The smoothing method used is Single Exponential. Single Exponential was chosen because it has a smaller error value than Double Exponential (13,46% < 14,07%). The result of the Single Exponential forecasting for 2023 period is 1.152 tons, 736 tons for the minimum production and 1.567 tons for the maximum production.